I think u know elementry trigo

Geometry Level 3

If tan θ = x 1 4 x \tan\theta = x - \dfrac1{4x} for x 0 x\ne 0 , express sec θ tan θ \sec\theta- \tan\theta in terms of x x .

2 x , 1 2 x -2x , \frac1{2x} 2 x 2x 2 x , 1 2 x 2x, \frac1{2x} 1 2 x , 2 x -\frac1{2x}, 2x

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Louis W
Aug 27, 2015

tan θ = x 1 4 x \tan \theta=x-\frac{1}{4x} 1 + tan 2 θ = sec 2 θ \color{#D61F06}{1+\tan^{2}\theta=\sec^{2}\theta} 1 + ( x 1 4 x ) 2 = sec 2 θ \color{#D61F06}{\Rightarrow}\color{#333333} 1+(x-\frac{1}{4x})^{2}=\sec^{2}\theta 1 + x 2 1 2 + 1 16 x 2 = sec 2 θ x 2 + 1 2 + 1 16 x 2 = sec 2 θ \color{#D61F06}{\Rightarrow}\color{#333333}1+x^{2}-\frac{1}{2}+\frac{1}{16x^{2}}=\sec^{2}\theta\color{#D61F06}{\Rightarrow}\color{#333333}x^{2}+\frac{1}{2}+\frac{1}{16x^{2}}=\sec^{2}\theta ( x + 1 4 x ) 2 = sec 2 θ sec θ = ± ( x + 1 4 x ) \color{#D61F06}{\Rightarrow}\color{#333333} (x+\frac{1}{4x})^{2}=\sec^{2}\theta\color{#D61F06}{\Rightarrow}\color{#333333} \sec \theta=\pm(x+\frac{1}{4x}) 1 ) sec θ tan θ = ( x + 1 4 x ) ( x 1 4 x ) = 1 2 x 1)\space\space\sec \theta-\tan \theta=(x+\frac{1}{4x})-(x-\frac{1}{4x})=\color{#3D99F6}{\frac{1}{2x}} 2 ) sec θ tan θ = ( x + 1 4 x ) ( x 1 4 x ) = 2 x 2)\space\space\sec \theta-\tan \theta=-(x+\frac{1}{4x})-(x-\frac{1}{4x})=\color{#3D99F6}{-2x}\color{#333333}\space\space\space\Box

Wesley Engers
Sep 5, 2015

First we'll combine into one fraction.

t a n θ = 4 x 2 1 4 x tan \theta = \frac{4x^2-1}{4x}

t a n θ = o p p o s i t e a d j a c e n t tan \theta = \frac{opposite}{adjacent}

We use the above triangle and the Pythagorean Theorem to solve for y.

( 4 x 2 1 ) 2 + ( 4 x ) 2 = y 2 (4x^2 - 1)^2 + (4x)^2 = y^2

16 x 4 + 8 x 2 + 1 = y 2 16x^4 +8x^2 +1 = y^2

( 4 x 2 + 1 ) 2 = y 2 (4x^2 +1)^2 = y^2

y = ± ( 4 x 2 + 1 ) y= \pm (4x^2 +1)

We know s e c θ = h y p o t e n u s e a d j a c e n t sec \theta = \frac{hypotenuse}{adjacent}

s e c θ = y 4 x = ± ( 4 x 2 + 1 ) 4 x sec \theta = \frac{y}{4x} = \frac{\pm(4x^2+1)}{4x}

Thus (plus version),

s e c θ tan θ = 4 x 2 + 1 4 x 4 x 2 1 4 x = 1 2 x sec \theta - \tan \theta = \frac{4x^2+1}{4x} - \frac{4x^2-1}{4x} = \frac{1}{2x}

OR (minus version)

s e c θ tan θ = ( 4 x 2 + 1 ) 4 x 4 x 2 1 4 x = 2 x sec \theta - \tan \theta = \frac{-(4x^2+1)}{4x} - \frac{4x^2-1}{4x} = -2x

nice solution

Sushil Kumar - 5 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...